Beyond opinion : living the faith that we defend - Zacharias, Ravi K. (Nashville : Thomas Nelson, 2007)
Addresses issues such as the validity of the Bible, the hypocrisy of its followers, and the need to make a new statement on faith, allowing Christians everywhere to simultaneously defend the faith and be transformed by it into people of compassion.
Postmodern challenges to the Bible / Amy Orr-Ewing -- Chalenges from atheism / Alister McGrath -- Challenges from youth / Alison Thomas -- Challenges from Islam / Sam Soloman -- Challenges from Eastern religions / L.T. Jeyachandran -- Challenges from science / John Lennox -- Conversational apologetics / Michael Ramsden -- Broader cultural and philosophical challenges / Joe Boot -- Existential challenges of evil and suffering / Ravi Zacharias -- Cross-cultural challenges / I'Ching Thomas -- The Trinity as a paradigm for spiritual transformation / L.T. Jeyachandran -- The role of doubt and persecution in spiritual transformation / Stuart McAllister -- Idolatry, denial, and self-deception: hearts on pilgrimage through the valleys / Danielle DuRant -- The Church's role in apologetics and the development of the mind ; Apologetics for today / Ravi Zacharias.
Includes bibliographical references (p. 343-360).
Keywords: Apologetics; Christianity and other religions